2023
DOI: 10.3389/fbioe.2023.1211143
|View full text |Cite
|
Sign up to set email alerts
|

A comparative recognition research on excretory organism in medical applications using artificial neural networks

Abstract: Purpose: In the contemporary era, a significant number of individuals encounter various health issues, including digestive system ailments, even during their advanced years. The major purpose of this study is based on certain observations that are made in internal digestive systems in order to prevent severe cause that usually occurs in elderly people.Approach: To solve the purpose of the proposed method the proposed system is introduced with advanced features and parametric monitoring system that are based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Furthermore, a study of 143 participants measured the adoption of shopping online via both websites and mobile shopping. The results show that mobile apps are more adopted in terms of accessibility [7,8].…”
Section: Overview Of Research In the Area Of Mobile Commercementioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, a study of 143 participants measured the adoption of shopping online via both websites and mobile shopping. The results show that mobile apps are more adopted in terms of accessibility [7,8].…”
Section: Overview Of Research In the Area Of Mobile Commercementioning
confidence: 96%
“…Secure communication: Along with cloud storage of data, there is a secure communication protocol that helps prevent eavesdropping and man-in-themiddle attacks. (8). Code obfuscation: Obfuscating the code can make it harder for attackers to reverse engineer the app and find vulnerabilities.…”
Section: Cyber Security Considerationsmentioning
confidence: 99%
“…While using BLE access points for location tracking within the rehabilitation wards, we found that only 284 out of the 43 measurements (82.8%) achieved a data-acquisition rate exceeding 90%. This indicates that data loss remains a challenge that needs addressing, which is similar to other medical-sensor-network systems (Selvarajan et al, 2023). This data loss could be due to equipment malfunctions, such as battery depletion, interference from electromagnetic shields in the environment, and human errors.…”
Section: Data Loss Of Location Trackingmentioning
confidence: 98%
“…Other communication units are not required in the representation scenarios due to the flexibility of data points being expanded above the stated ranges. In addition, fuzzy offers a hard clustering of data points with precise membership functions in comparison to other clustering methods ( Al-ani et al, 2023 ; Selvarajan & Manoharan, 2023 ). As a result, Eq.…”
Section: Research Gap and Motivationmentioning
confidence: 99%